لترقية الطالبات على فهم كتاب القراءة الرشيدة بمعهد الزهرة العصري بيرون- آتشيه STUDY استخدام الأسلوب - Phonna, Raihanil; Suhaimi, Suhaimi; Yulistri, Yulistri (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
Learning at Modern Pesantren Al-Zahrah with theory of branches and among the subjects taught is Muthalaah with the Book al-Qiraatu ar-raasyiidah. The Purpose of Muthalaah's Learning in Modern Pesantren Al-Zahrah is a form of reading practice, justifying and enriching the language and deepening Qawaid Nahwu-Sharf. Muthalaah's learning process usually takes place with lecture methods and sometimes some teachers use the Jigsaw method in the learning process. The percentage of outcomes of the learning is 40% of students complete and the remaining 60% unfinished. This is evidenced by the acquisition of their test scores under the category below average. They are not able to answer questions about text content and do not understand certain words. Based on this problem Researchers want to conduct research with the title "Use of STUDY Techniques to improve students' ability in understanding the Book of Al-Qiraatu Ar-Rasyiidah (Experimental Research on Class II MTsS Pesantren Modern Al-Zahrah Bireuen-Aceh)" The purpose of this thesis is to knowing the effectiveness of the students' ability to understand Al-Qiraatu Ar-Rasyiidah book by using STUDY technique and to know the use of STUDY Technique in teaching and learning process of Al-qiraatu Ar-Rasyiidah in Modern Pesantren Al-Zahrah. The research method used, Researchers choose Experimental Research, with data collection methods through Pre test, Post Test Direct observation and Questionnaire. The population of this study is all students of Modern Pesantren Al-Zahrah as many as 1225 students, while the sample Researchers chose class II B as many as 36 students. And The results of research obtained by the researcher that the use of STUDY techniques effective to improve the ability of students in understanding the book Al-Qiraatu Ar-Rasyiidah proven by the acquisition value to 8.82 greater than the value of significance table 5% that is 2.03 and table significance 1 % that is 2.72 and that STUDY technique give positive influence to student in learning book al-qiraatu ar-rasyiidah.